Does union membership matter? Political participation, attachment to democracy and generational change. (September 2020) - Turner, Thomas; Ryan, Lorraine; O'Sullivan, Michelle
We examine whether trade union membership enhances political activism and beliefs in the democratic system, and argue that trade unions and union membership are more likely to develop workers' capacities to participate as citizens in the democratic process. Union members are more likely to engage in political activities and hold more positive attitudes towards democracy than non-union respondents across 11 stable European democracies with varying levels of union density and collective bargaining coverage. A notable trend is the decline over generations of the positive gap in political participation levels between union and non-union workers. It appears that the effects of union membership for political participation and attitudes to democracy, though still significant, are less salient for the 1980s generation.